Radiotherapy-induced alterations in tumor microenvironment: metabolism and immunity - Chen, Jinpeng; Wang, Sheng; Ding, Yue; Xu, Duo; Zheng, Shiya (Frontiers in Cell and Developmental Biology, 2025)
Tumor metabolism plays a pivotal role in shaping immune responses within the tumor microenvironment influencing tumor progression, immune evasion, and the efficacy of cancer therapies. Radiotherapy has been shown to impact both tumor metabolism and immune modulation, often inducing immune activation through damage-associated molecular patterns and the STING pathway. In this study, we analyse the particular characteristics of the tumour metabolic microenvironment and its effect on the immune microenvironment. We also review the changes in the metabolic and immune microenvironment that are induced by radiotherapy, with a focus on metabolic sensitisation to the effects of radiotherapy. Our aim is to contribute to the development of research ideas in the field of radiotherapy metabolic-immunological studies.